2013
DOI: 10.4049/jimmunol.1300396
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor T-bet Regulates Parasitemia and Promotes Pathogenesis duringPlasmodium bergheiANKA Murine Malaria

Abstract: The pathogenesis of experimental cerebral malaria (ECM) is an immunologic process, mediated in part by Th1 CD4+ T cells. However, the role of the Th1 CD4+ T cell differentiation program on the ability to control parasitemia and susceptibility to ECM disease during blood stage malaria has never been assessed directly. Using the Plasmodium berghei ANKA murine model of ECM and mice deficient for the transcription factor T-bet (the master regulator of Th1 cells) on the susceptible C57BL/6 background, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 62 publications
0
65
2
Order By: Relevance
“…In rodent systems, control of the acute phase of Plasmodium chabaudi infection is thought to be at least partially controlled by CD4 + T cells (Taylor-Robinson et al 1993), and ironically, the same cells may also contribute to pathology in the host (Oakley et al 2013). It is interesting to note that survivors in the present experiment maintained WBCs below or at the level of control birds throughout the experiment while nonsurvivors appeared to drive WBC concentrations up at certain times (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In rodent systems, control of the acute phase of Plasmodium chabaudi infection is thought to be at least partially controlled by CD4 + T cells (Taylor-Robinson et al 1993), and ironically, the same cells may also contribute to pathology in the host (Oakley et al 2013). It is interesting to note that survivors in the present experiment maintained WBCs below or at the level of control birds throughout the experiment while nonsurvivors appeared to drive WBC concentrations up at certain times (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Upon parasite inoculation, and after the prepatent period, which corresponds to the few days before parasites appear in the blood, birds typically undergo an Bacute phase^of infection leading to a surge of parasites in the peripheral blood (peak parasitemia). Infection usually is rapidly controlled by the host immune system in birds (Atkinson et al 2001), as well as in rodents (Taylor-Robinson et al 1993;Oakley et al 2013) and humans (Good et al 2005). Following this immune activation, birds enter a Bchronic phase^of infection characterized by a longer period of low parasitemia which may last the lifetime of the individual (Bishop et al 1938;Valkiūnas 2005;, but see Latta andRicklefs 2010 andWood et al 2013 for evidence that hosts can clear infections at least from the peripheral blood).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, there have been no reports of increased incidences of bacterial infections or vaccine unresponsiveness in HBsAg þ children. In contrast, reports have shown that, in patients with malaria, HBsAg positivity is associated with lower parasitemia (Andrade et al 2011), or episodes of cerebral malaria, that is, a pathological manifestation indicative of a heightened Th1 response against the parasite (Oakley et al 2013). To add to the confusion, a recent report has suggested that HBsAg, instead of having suppressive role, might directly induce a heightened Th17 response through activation of IL-23 on macrophages .…”
Section: Immunomodulatory Roles Of Hbv Antigensmentioning
confidence: 99%
“…MMP-2 over-expression is observed in certain infections where eradication and control of immunopathogenesis rely on the development of protective type-2 responses (Oakley et al, 2013; Sauer et al, 2013). For instance, various parasites including plasmodium (Lima et al, 2012) and toxoplasma (Lu and Lai, 2013) species can trigger MMP-2 over-expression.…”
Section: Introductionmentioning
confidence: 99%